Gomphonema yaominae sp. nov. Li, a new species of diatom (Bacillariophyta) from lakes near Yangtze River, China - Gong, Zhijun; Li, Yanling (Phytotaxa, 2012)
This paper describes the new species Gomphonema yaominae sp. nov. from lakes in the lower reaches of Yangtze River, China. The description is based on data derived from light and scanning electron microscopy. The main features of Gomphonema yaominae are: lanceolate valves, which gradually taper towards the headpole and more abruptly taper from the valve centre towards the footpole; a rounded headpole; a narrowly rounded footpole; a narrow and lanceolate axial area (sternum); an undulate and distinctly lateral raphe; and radiate striae. It is common to abundant on water plants in the samples examined herein.